Pergaulan Remaja Dalam Tinjauan Filsafat Etika (Fenomena Di Desa Karang Baru Kecamatan Datuk Tanah Datar Kabupaten Batubara) - Sutiara, Leny (UIN Sumatera Utara, 2024)
This research is entitled Youth association in a review of ethical philosophy (a phenomenon in Karang Baru Village, Datuk Tanah Datar District, Coal District). Intercourse in adolescence is an important thing to continue to be monitored properly, and this becomes the focal point of the source of the problem that is used as the background in this research and is used as a form of scientific work in the form of a thesis. This thesis describes the subject matter of the research problem which is divided into 3 sub-problems, namely, first discussing how the form of youth association in Karang Baru Village, Datuk Tanah Datar District, Coal Regency, secondly discussing what factors influence ethics in relationships among teenagers in Indonesia. Karang Baru Village, Datuk Tanah Datar District, Batubara Regency, the third discusses how the social ethics of juvenile delinquency in Karang Baru Village. For this reason, this thesis aims to find out some of the problems that have been exposed in the formulation of the problem in order to get the results of a study. The research method used is descriptive qualitative method or field research (Field Research) and the type of approach used is a phenomenological approach. The data sources used are primary data sources, namely adolescents aged 13-16 years and secondary data sources, namely community leaders from Karang Baru village. In this study the authors collect data through field observations, interviews, and documentation. The results of this study indicate that in the association of adolescents there are several ethics that need to be applied so that in their association they can be directed to a better realm. And the phenomenon obtained in this study is that there are several teenagers who fall into the category of good association and bad association. Good association is that various teenagers still want to join in positive activities in the village such as helping mothers and fathers in religious activities, carrying out routine activities to clean the mosque every Friday. While the bad association is that some teenagers often do reckless behavior on the streets that are always passed by the community, hang out with the opposite sex without any restrictions, often hang out together and play online games without remembering the time, so that from this form of association many are the reasons for this. behavior of a child towards his parents is not good.